Towards inhibitors of glycosyltransferases: A novel approach to the synthesis of 3-acetamido-3-deoxy-D-psicofuranose derivatives - Bella, Maroš; Koóš, Miroslav; Lin, Chun-Hung (Beilstein Journal of Organic Chemistry, 2015)
A novel synthetic strategy leading to 3-acetamido-3-deoxy-D-psicofuranose 9 is presented. The latter compound, after some manipulations, was transformed into fully protected 3-acetamido-3-deoxy-D-psicofuranose 11 as a potential substrate for the synthesis of N-acetylglucosaminyltransferase inhibitors designed by computational methods. After the attempted thioglycosylation of 11 with EtSH in the presence of BF3·OEt2, 2-methyloxazoline derivatives 13 and 14 were isolated.
Keywords: glycosyltransferases; inhibitors; D-psicofuranose; synthesis; thioglycosylation

Essentials of Glycobiology - Varki, A.; Cummings, R. D.; Esko, J. D.; Freeze, H. H.; Stanley, P. (Cold Spring Harbor Laboratory Press, 2009)

(untitled) - Weis, W. I.; Taylor, M. E.; Drickamer, K. (Immunol. Rev., 1998)

New comprehensive biochemistry - Montreuil, J.; Vliegenthart, J. F. G.; Schachter, H. (Glycoproteins and disease, 1996)

(untitled) - Marquardt, T.; Freeze, H. (Biol. Chem., 2001)

(untitled) - Hakomori, S. (Proc. Natl. Acad. Sci. U. S. A., 2002)

(untitled) - Dennis, J. W.; Laferté, S.; Waghorne, C.; Breitman, M. L.; Kerbel, R. S. (Science, 1987)

(untitled) - Ünligil, U. M.; Rini, J. M. (Curr. Opin. Struct. Biol., 2000)

(untitled) - Breton, C.; Fournel-Gigleux, S.; Palcic, M. M. (Curr. Opin. Struct. Biol., 2012)

(untitled) - Hirsch, J.; Koóš, M.; Tvaroška, I. (Chem. Pap., 2009)

(untitled) - Raab, M.; Kozmon, S.; Tvaroška, I. (Carbohydr. Res., 2005)

(untitled) - Look, G. C.; Fotsch, C. H.; Wong, C.-H. (Acc. Chem. Res., 1993)

(untitled) - Sears, P.; Wong, C.-H. (Proc. Natl. Acad. Sci. U. S. A., 1996)

(untitled) - Wang, R.; Steensma, D. H.; Takaoka, Y.; Yun, J. W.; Kajimoto, T.; Wong, C.-H. (Bioorg. Med. Chem., 1997)

(untitled) - Sears, P.; Wong, C.-H. (Angew. Chem., Int. Ed., 1999)

(untitled) - Elhalabi, J. M.; Rice, K. G. (Curr. Med. Chem., 1999)

(untitled) - Waldscheck, B.; Streiff, M.; Notz, W.; Kinzy, W.; Schmidt, R. R. (Angew. Chem., Int. Ed., 2001)

(untitled) - Compain, P.; Martin, O. R. (Bioorg. Med. Chem., 2001)

(untitled) - Tvaroška, I.; André, I.; Carver, J. P. (J. Am. Chem. Soc., 2000)

(untitled) - Tvaroška, I.; André, I.; Carver, J. P. (Glycobiology, 2003)

(untitled) - Schmidt, O. T. (Methods Carbohydr. Chem., 1963)

(untitled) - Shen, X.; Wu, Y.-L.; Wu, Y. (Helv. Chim. Acta, 2000)

(untitled) - Frick, W.; Krülle, T.; Schmidt, R. R. (Liebigs Ann. Chem., 1991)

(untitled) - Lin, W.; Zhang, X.; He, Z.; Jin, Y.; Gong, L.; Mi, A. (Synth. Commun., 2002)

SMART & SAINT (Bruker AXS Inc., 2003)

SADABS, Version 2.10 (University of Göttingen, 2003)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A, 2008)

(untitled) - Gruene, T.; Hahn, H. W.; Luebben, A. V.; Meilleur, F.; Sheldrick, G. M. (J. Appl. Crystallogr., 2013)

(untitled) - Cremer, D.; Pople, J. A. (J. Am. Chem. Soc., 1975)

(untitled) - McNaught, A. D. (Pure Appl. Chem., 1996)